A checklist of the vascular plants of the lowland savannas of Belize, Central America - Goodwin, Zoë A.; Lopez, German N.; Stuart, Neil; Bridgewater, Samuel G.m.; Haston, Elspeth M.; Cameron, Iain D.; Michelakis, Dimitris; Ratter, James A.; Furley, Peter A.; Kay, Elma; Whitefoord, Caroline; Solomon, James; et al. (Phytotaxa, 2013)
Lowland savannas, covering an area of 2,342 km2, form the third largest ecosystem in Belize yet are unevenly and therefore poorly represented in the country’s protected area system. Based on more than 5,700 herbarium collections, a checklist of 957 species of vascular plants is presented for this ecosystem representing ca. 28% of the Belizean flora, of which 54 species are new records for the country. Of the 41 species of plants known to be endemic to Belize, 18 have been recorded within the lowland savanna, and nine species are listed in The World Conservation Union (IUCN) 2010 Red List of Threatened Species. Of the total savanna ecosystem flora, 339 species are characteristic of the open savanna, whilst 309 and 114 species are more frequent in forest and wetland areas respectively. Most species (505, 53% of the lowland savanna flora) are herbaceous. Although the lowland savanna has been relatively well collected, there are geographical biases in botanical sampling which have focused historically on the savannas in the centre and the north of the country. A brief review of the collecting history of the lowland savanna is provided, and recommendations are given on how future collecting efforts may best be focused. The lowland savanna is shown to be a significant regional centre of plant diversity.